2017
DOI: 10.5152/iao.2017.2027
|View full text |Cite
|
Sign up to set email alerts
|

A New Hypothesis on the Frequency Discrimination of the Cochlea

Abstract: OBJECTIVE:Medial olivocochlear efferent (MOCE) neurons innervate outer hair cells (OHCs) of the cochlea, which in turn leads to basilar membrane motion. We hypothesized that MOCE-induced alterations in basilar membrane motion, independent of traveling waves, is responsible for the cochlear frequency discrimination of sound. MATERIALS and METHODS:Eleven guinea pigs underwent bilateral otoscopic and audiologic evaluations under general anesthesia. The study comprised two parts. Part I (n=11) included spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These animals were housed at 16-21°C under a 12-h light-dark cycle and fed ad libitum pellet. The reason why we chose to use guinea pigs as a model in our study is that they are widely used in otological studies [Albuquerque et al, 2009], and the experience of guinea pigs in terms of electrophysiological measurements and histopathological examinations was well gained in previous experimental inner ear studies of our clinic [Bulut et al, 2017]. The guinea pigs underwent electrophysiological measurements under general an-aesthesia, which was achieved by intramuscular administration of ketamine hydrochloride 40 mg/kg + xylazine hydrochloride 5 mg/kg.…”
Section: Animalsmentioning
confidence: 99%
“…These animals were housed at 16-21°C under a 12-h light-dark cycle and fed ad libitum pellet. The reason why we chose to use guinea pigs as a model in our study is that they are widely used in otological studies [Albuquerque et al, 2009], and the experience of guinea pigs in terms of electrophysiological measurements and histopathological examinations was well gained in previous experimental inner ear studies of our clinic [Bulut et al, 2017]. The guinea pigs underwent electrophysiological measurements under general an-aesthesia, which was achieved by intramuscular administration of ketamine hydrochloride 40 mg/kg + xylazine hydrochloride 5 mg/kg.…”
Section: Animalsmentioning
confidence: 99%
“…In studies on the temporal bone performed in human subjects who were exposed to chronic occupational noise for 30 years, the loss of internal hairy cells in the basal rotation of the cochlea was limited, but a significant loss of external hairy cells (DTH) was observed (20). In experimental animal studies (21)(22)(23), the primary target cell group has been reported to be DTH at acute noise-induced hearing loss. Together with the increase in the duration and intensity of the noise, this causes the structural deterioration in the internal hairy cells and the entire Corti Organ (23).…”
Section: Introductionmentioning
confidence: 99%